Transcriptional Regulation of Early T-Lymphocyte Development in Thymus - Bao, Xueyang; Qin, Yingyu; Lu, Linrong; Zheng, Mingzhu (Frontiers in Immunology, 2022)
T-lymphocytes play crucial roles for maintaining immune homeostasis by fighting against various pathogenic microorganisms and establishing self-antigen tolerance. They will go through several stages and checkpoints in the thymus from progenitors to mature T cells, from CD4-CD8- double negative (DN) cells to CD4+CD8+ double positive (DP) cells, finally become CD4+ or CD8+ single positive (SP) cells. The mature SP cells then emigrate out of the thymus and further differentiate into distinct subsets under different environment signals to perform specific functions. Each step is regulated by various transcriptional regulators downstream of T cell receptors (TCRs) that have been extensively studied both in vivo and vitro via multiple mouse models and advanced techniques, such as single cell RNA sequencing (scRNA-seq) and Chromatin Immunoprecipitation sequencing (ChIP-seq). This review will summarize the transcriptional regulators participating in the early stage of T cell development reported in the past decade, trying to figure out cascade networks in each process and provide possible research directions in the future.